Specific signaling pathways mediated programmed cell death in tumor microenvironment and target therapies - Chengpeng Sun; Jiawei Gui; Yilei Sheng; Le Huang; Xingen Zhu; Kai Huang (Discover Oncology)
Abstract Increasing evidence has shown that programmed cell death (PCD) plays a crucial role in tumorigenesis and cancer progression. The components of PCD are complex and include various mechanisms such as apoptosis, necroptosis, alkaliptosis, oxeiptosis, and anoikis, all of which are interrelated in their functions and regulatory pathways. Given the significance of these processes, it is essential to conduct a comprehensive study on PCD to elucidate its multifaceted nature. Key signaling pathways, particularly the caspase signaling pathway, the RIPK1/RIPK3/MLKL pathway, and the mTOR signaling pathway, are pivotal in regulating PCD and influencing tumor progression. In this review, we briefly describe the generation mechanisms of different PCD components and focus on the regulatory mechanisms of these three major signaling pathways within the context of global PCD. Furthermore, we discuss various tumor therapeutic compounds that target different signaling axes of these pathways, which may provide novel strategies for effective tumor therapy and help improve patient outcomes in cancer treatment.